A Specific Point Mutant at Position 1 of the Influenza Hemagglutinin Fusion Peptide Displays a Hemifusion Phenotype - Qiao, Hui (The American Society for Cell Biology, 1999)
We showed previously that substitution of the first residue of the influenza hemagglutinin (HA) fusion peptide Gly1 with Glu abolishes fusion activity. In the present study we asked whether this striking phenotype was due to the charge or side-chain volume of the substituted Glu. To do this we generated and characterized six mutants with substitutions at position 1: Gly1 to Ala, Ser, Val, Glu, Gln, or Lys. We found the following. All mutants were expressed at the cell surface, could be cleaved from the precursor (HA0) to the fusion permissive form (HA1-S-S-HA2), bound antibodies against the major antigenic site, bound red blood cells, and changed conformation at low pH. Only Gly, Ala, and Ser supported lipid mixing during fusion with red blood cells. Only Gly and Ala supported content mixing. Ser HA, therefore, displayed a hemifusion phenotype. The hemifusion phenotype of Ser HA was confirmed by electrophysiological studies. Our findings indicate that the first residue of the HA fusion peptide must be small (e.g., Gly, Ala, or Ser) to promote lipid mixing and must be small and apolar (e.g., Gly or Ala) to support both lipid and content mixing. The finding that Val HA displays no fusion activity underscores the idea that hydrophobicity is not the sole factor dictating fusion peptide function. The surprising finding that Ser HA displays hemifusion suggests that the HA ectodomain functions not only in the first stage of fusion, lipid mixing, but also, either directly or indirectly, in the second stage of fusion, content mixing.